Global burden of stroke attributable to high systolic blood pressure in 204 countries and territories, 1990–2019 - Li, Junxiao; Zhong, Qiongqiong; Yuan, Shixiang; Zhu, Feng (Frontiers in Cardiovascular Medicine, 2024)
Background: High systolic blood pressure (HSBP) is severely related to stroke, although the global burden of stroke associated with HSBP needs to be understood.: Data derived from the Global Burden of Disease, Injuries, and Risk Factors Study was used to analyze deaths, disability-adjusted life years (DALYs), age-standardized rates of mortality (ASMR), age-standardized rates of DALY (ASDR), and estimated annual percentage change (EAPC).Results: Globally, 52.57% of deaths and 55.54% of DALY from stroke were attributable to HSBP in 2019, with higher levels in males; the ASMRs and ASDRs in 1990-2019 experienced a decline of 34.89% and 31.71%, respectively, with the highest ASMR-and ASDR-related EAPCs in females.The middle socio-demographic index (SDI) regions showed the most numbers of deaths and DALY in 2019 and 1990, with a decline in ASMR and ASDR; East Asia shared over 33% of global deaths and DALY; Central Asia shared the highest ASMR and ASDR; high-income Asia Pacific experienced the highest decline in the ASMR-and ASDR-related EAPCs. Central Asia and Southeast Asia had the highest percentages for deaths and DALY, respectively; with more ASMR in high-middle SDI; the SDI and human development index were negatively associated with ASMR/ASDR and ASMR-/ASDR-related EAPCs in 2019.Global deaths and DALYs but their age-standardized rates of stroke attributable to HSBP were on the rise over the past three decades; its disease burden focused especially on males aged 70 and older in East, Central, and Southeast Asia, and the middle to high SDI regions.